Awareness Regarding Diabetes Risk Factors, Prevention and Management among Community Members in Diyala/Baqubah - Abdul Karim, Rania Ayad; Habib, Huda Adnan (AL-Kindy College Medical Journal, 2022)
Background: Background: Diabetes mellitus is a life-threatening disease. Global prevalence of diabetes mellitus is increasing rapidly providing a worrying indication and major threat to global health unless interventions are created through community awareness and knowledge regarding different aspect of DM. Aims: To assess the level of awareness regarding diabetes risk factors, prevention and management among community members in Baqubah city and to identify any association between awareness level and some variables. Methods: Across sectional study was carried out from the 1st of January - 30th of November 2019 in all primary health care centers (six centers) in center of Baqubah city. A convenient sample of 400 participants who attended the health centers during the study period and eligible to inclusion criteria were included. Data were collected vie direct interview with a structural questionnaire that include personal data, questions regarding knowledge, regard diabetes definition, prevention, risk factor, management and control. Results: Good diabetes awareness were reported among 50% of studied. A significant statistical association were found between good awareness and age of 20-30years, more than secondary school education, high family income and positive family history of diabetes with the following (52, 34, 35 & 68) % respectively. Conclusion: Good diabetes awareness was dominant and was significantly associated with middle age group, higher education and positive family history of diabetes. an educational health programs that tackles area of weakness about awareness of diabetes mellitus need to be implemented on the governmental level.